1991
DOI: 10.1002/lary.1991.101.s54.1
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mandibular Reconstruction: Analysis of 64 Cases and Evaluation of Interface Radiation Dosimetry on Bridging Plates

Abstract: The combination of a myocutaneous flap or free cutaneous tissue transfer with a three‐dimensional bendable reconstruction plate either of stainless steel or titanium has provided very satisfactory results in primary restoration of mandibular defects following surgical resections in irradiated patients or in those who require postoperative radiotherapy. Sixty‐four cases have been treated and evaluated prospectively using this technique. Fifty‐three of the patients had the soft‐tissue defect restored with a myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 67 publications
(28 reference statements)
1
32
1
Order By: Relevance
“…9 Of the head and neck reconstructive materials which have previously been tested, stainless steel and Vitallium appear to have the greatest electron backscattering effect, with reports of dose enhancements from 15% to 36% in phantom tissue models using a 6MV energy radiation source. 1,2,4 The present investigation supports the use of cpt or tia in patients expected to undergo radiotherapy (as previously suggested by Delacroix 3 ) since these materials have a reduced effect on radiation dose distribution when compared with stainless steel. Still further reduction in adverse radiotherapy effects may be achieved through use of reconstructive devices of lower atomic number.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…9 Of the head and neck reconstructive materials which have previously been tested, stainless steel and Vitallium appear to have the greatest electron backscattering effect, with reports of dose enhancements from 15% to 36% in phantom tissue models using a 6MV energy radiation source. 1,2,4 The present investigation supports the use of cpt or tia in patients expected to undergo radiotherapy (as previously suggested by Delacroix 3 ) since these materials have a reduced effect on radiation dose distribution when compared with stainless steel. Still further reduction in adverse radiotherapy effects may be achieved through use of reconstructive devices of lower atomic number.…”
Section: Discussionsupporting
confidence: 78%
“…Studies have consistently found increased radiation dosage in front of (anterior to) and attenuated doses behind (posterior to) metallic plates. [1][2][3][4] These findings are explained by the ''interface effect'' which occurs when gamma rays cross the boundary between materials of different atomic number and subsequently cause scattering of secondary electrons. Changes in the fluence of secondary electrons produce radiation-dose enhancement on the side facing the beam (backscatter) and attenuation of the gamma rays on the interface side distal to the beam (transmission).…”
Section: Discussionmentioning
confidence: 90%
“…Kin and Donoff 24 and Klotch and Prein 20 reported increased complication rates in irradiated fields, whereas others have reported no adverse effect. 22,25,26 According to Choi et al, radiation therapy does not impact local complication rates after free flap reconstruction for head and neck cancer. 25 In a study of 100 patients who underwent free fibula flap reconstruction of the mandible, 54% of 28 patients in the no radiotherapy group, 65% of 37 patients in the preoperative radiotherapy group, and 46% of 35 patients in postoperative radiotherapy group had complications of any severity.…”
Section: Discussionmentioning
confidence: 98%
“…Major complication rates range from 15% to 45% in these series. [20][21][22][23][24] These include fistulas, infection, loose hardware, and plate exposure. Contradictory reports exist in the literature on the role of radiation on plate and osteosynthesis related complications.…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated with microvascular free flap reconstruction of the mandible. [23][24][25][26][27] Predictable implant placement in VBCFFs also allows for successful prosthetic rehabilitation. [28][29][30][31][32] Unlike mandible reconstruction, in which VBCFFs are necessary for discontinuity defects, limited defects of the palate can be reconstructed with a soft tissue free flap, provided that the native maxilla maintains the stable base necessary for function.…”
mentioning
confidence: 99%